Natural cytotoxicity in immunodeficiency diseases: Preservation of natural killer activity and the in vivo appearance of radioresistant killing - Pierce, Glenn F.; Polmar, Stephen H.; Schacter, Bernice Z.; Brovall, Charlotte; Hornick, David L.; Sorensen, Ricardo U. (Human immunology, 1986)
We studied spontaneous natural killer (NK) cell activity and radiation-resistant NK mediated cytotoxicity in four patients with clinically documented severe combined immune deficiency disease (SCID), and in one subject each with intestinal lymphangiectasia and cartilage-hair hypoplasia. We observed the preservation of spontaneous NK activity in all patients despite the presence of profound B- and T-lymphocytopenia and clinical immunodeficiency. NK activity was associated with relatively normal circulating numbers of OKM1 + lymphocytes, a population known to contain NK effectors. Spontaneous NK activity resistant to 3000 rad was increased in all patients, indicating the presence of activated natural killer cells in vivo. The concept of a chronically activated immune system in these patients was further supported by the presence of increased Ia positive T cells in all subjects tested, suggesting that radioresistant NK activity may be a useful parameter to measure when assessing in vivo immune activation. Our data, as well as that of others, supports the hypothesis that at least one population of NK cells is a distinct lineage arising at the differentiation level of myeloid and lymphoid stem cells in the bone marrow.